Bioactive compounds of medicinal plants : properties and potential for human health - Ayeleso, Ademola Olabode; Goyal, Megh Raj; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
This volume sheds new light on the immense potential of medicinal plants for human health from different technological aspects. It presents new research on bioactive compounds in medicinal plants that provide health benefits, including those that have proven especially effective in treating and managing diabetes mellitus and hypertension. It looks at the medicinal properties, antioxidant capacity, and antimicrobial activity of plants and provides scientific evidence on the use of medicinal plants in the treatment of certain diseases. Many of the plants described in the chapters are easily accessible and are believed to be effective with fewer side effects in comparison to modern drugs in the treatment of different diseases.
part PART I: BIOACTIVE COMPOUNDS IN MEDICINAL PLANTS AND HEALTH BENEFITS -- chapter 1 Phytochemistry and Antifungal Activity of Desmodium adscendens Root Extracts / Nwanekwu Kenneth Emeka -- chapter 2 Bioactive Compounds in Plants and Their Antioxidant Capacity / Oluyemisi Elizabeth Adelakun -- chapter 3 Plants of the Genus Syzygium (Myrtaceae): A Review on Ethnobotany, Medicinal Properties, and Phytochemistry / Ian Edwin Cock -- part PART II: MEDICINAL PLANTS/PLANT PRODUCTS AND HEALTH PROMOTION -- chapter 4 Effects of Talinum triangulare on Hepatic Antioxidant Gene Expression Profile in Carbon Tetrachloride-Induced Rat Liver Injury / Gbenga Anthony Adefolaju -- chapter 5 Review on Potential of Seeds and Value-Added Products of Bambara Groundnut (Vigna subterranea): Antioxidant, Anti-Inflammatory, and Anti-Oxidative Stress / Yvonne Yeukai Murevanhema -- chapter 6 Antioxidant and Antimicrobial Activity of Opuntia Aurantiaca Lindl / Wilfred Mbeng Otang -- chapter 7 Dietary Intervention of Utazi (Gongrenema Latifolium) Supplemented Diet Using Wistar Male Rat Animal Brain Model / Esther Emem Nwanna -- part PART III: MEDICINAL PLANTS AND MANAGEMENT OF DIABETES MELLITUS -- chapter 8 Therapeutic Potentials of Selected Medicinal Plants in the Management of Diabetes Mellitus: A Review / Folorunso Adewale Olabiyi -- chapter 9 Medicinal Activities of Anchomanes Difformis and Its Potential in the Treatment of Diabetes Mellitus and Other Disease Conditions: A Review / Toyin Dorcas Udje -- chapter 10 Screening of Different Extracts of Ageratum Conyzoides for Inhibition of Diabetes-Related Enzymes / Mutiu Idowu Kazeem -- chapter 11 Potential of Catharanthus Roseus and Punica Granatum in the Management and Treatment of Diabetes Mellitus and Its Complications. Mediline Goboza, Prisca Kachepe, Yapo Guillaume Aboua, / Oluwafemi Omoniyi Oguntibeju -- part PART IV: MEDICINAL PLANTS AND MANAGEMENT OF HYPERTENSION -- chapter 12 Ginger and Turmeric Supplemented Diet as a Novel Dietary Approach for Management of Hypertension: A Review / Ayodele Jacob Akinyemi.
Keywords: Botany; Complementary & Alternative Medicine; Diabetes Mellitus -- drug therapy; Materia medica, Vegetable; Pharmacology; Phytotherapy; Plant Extracts -- therapeutic use; Plants, Medicinal; MEDICAL / Pharmacology; MEDICAL / Pharmacology; MEDICAL / Alternative Medicine; Plants, Medicinal; Diabetes Mellitus -- drug therapy; Phytotherapy; Plant Extracts -- therapeutic use; Africa